Quality Assisted Living : Informing Practice Through Research - Morgan, Leslie A. (Springer Pub., 2012)
Considering that seventy-four million baby boomers will be the next generation of assisted living residents, there is a great need to create, sustain, and evaluate quality in these settings. Whereas most books focus on quality of care, this is the only volume to explicitly delve into the lives of those who inhabit assisted living facilities, seeking to understand and evaluate their perceived ideas of what constitutes quality of life. Quality Assisted Living provides results from a National Institute on Aging-funded study that gathered information from not only residents, but also staff and family members, who are considered experts who can better help us to understand how quality should be conceived and evaluated.